2022
DOI: 10.3390/hemato3040043
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphoproliferative Neoplasms of Uncertain Biological Significance: Report from the IV Workshop of the Italian Group of Hematopathology and Review of the Literature

Abstract: Lymphoproliferative neoplasms of uncertain biological significance are increasingly encountered due to widespread usage of immunophenotypic and molecular techniques. Considering that clearer biological criteria and patient management have been established for B-cell lymphoproliferative diseases of undetermined significance occurring in the peripheral blood, many issues are still obscure for early lesions detected in lymphoid tissues. Regardless that some categories of lymphoproliferative neoplasms of uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Confirmation of FL by Bcl2 stain is crucial. Atypical GCs for Bcl-2 − usually have only clusters of large centroblasts with aberrant mitosis and are not expressed for Bcl-2 by immunostaining 35 . Several studies have shown that lymphoid clones can still be detected even in the context of normal reactive GC and benign hyperplastic marginal regions by immunoglobulin gene rearrangement [36][37][38][39] .…”
Section: Abnormal Follicular Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirmation of FL by Bcl2 stain is crucial. Atypical GCs for Bcl-2 − usually have only clusters of large centroblasts with aberrant mitosis and are not expressed for Bcl-2 by immunostaining 35 . Several studies have shown that lymphoid clones can still be detected even in the context of normal reactive GC and benign hyperplastic marginal regions by immunoglobulin gene rearrangement [36][37][38][39] .…”
Section: Abnormal Follicular Patternsmentioning
confidence: 99%
“…Flow cytometry results demonstrated that FLBUS was not misinterpreted as it could only reflect B cells similar to FL. Recently, FLBUS has been proposed to show that these cases are not lymphomas but only look like lymphomas 31, 35 . Consistent with concerns that overdiagnosis of lymphoma leads to a patient's pessimism and may result in unnecessary treatment.…”
Section: Follicular Hyperplasia Relevant To Neoplasmmentioning
confidence: 99%